Exploring Diversity in Learning Behavior at University: Opportunities for Conceptualization - Малошонок, Наталья; Вилкова, Ксения; Дремова, Оксана (Voprosy obrazovaniâ, 2024)
Student learning behavior is often considered as a main predictor of learning outcomes at university. However, in previous studies, it has been conceptualized and measured only fragmentarily. Researchers focused on certain aspects of learning behavior, or tried to build a typology of behavioral patterns that oversimplified this phenomenon and could not describe and explain all its diversity. In this paper, we try to overcome the shortcomings of previous conceptualizations of learning behavior by building our own conceptual model for this concept. Based on the analysis of 119 semi-structured interviews with students from eight Russian universities, we identify five main characteristics of learning behavior that can be used to describe the majority of behavioral patterns at universities. They are the following: 1) academic diligence; 2) learning activity; 3) integration into the group; 4) conformity; 5) extracurricular activity. In the paper, we give the definition of learning behavior at university and its five aspects, as well as illustrate these aspects with quotations from interviews with students. The developed conceptual model can be used to develop tools for quantitative measurement of learning behavior.